Effect of Soaking Time of Thermoplastic Nylon Denture Base in Beta vulgaris L. Juice on Color Stability: Effect of Soaking Time of Thermoplastic Nylon Denture Base - Putranti, Dwi Tjahyaning; Marbun, Helen Saparingga (Universitas Syiah Kuala, 2025)
Thermoplastic nylon denture base material is known to be soluble in phenol compounds. Cancer patients are strongly advised to consume beetroot as a chemopreventive herb, as it contains flavonoids and betalains, which are phenolic compounds. The consumption of beetroot juice by users of thermoplastic nylon denture bases over a long period of time is associated with the color stability of these bases. The amount of color change depends on the accumulation of phenolic compounds and the absorption of color pigments. This study aimed to determine the effect of prolonged immersion of thermoplastic nylon denture bases in beetroot juice for 4, 8, and 12 days on color stability. The design of this study was a laboratory experiment with cylindrical samples measuring 20 x 3 mm, comprising 30 samples divided into 6 groups: the control group and the immersion group using beetroot juice (Beta vulgaris L.). Samples soaked in beetroot juice for 4, 8, and 12 days will be measured for color stability using a colorimeter. were analyzed using a one-way ANOVA and LSD (Least Significant Difference) post hoc tests. The results showed that immersion time of thermoplastic nylon denture bases in beetroot (Beta vulgaris L.) juice affected color stability (p = 0.0001; p < 0.05). This study demonstrates that immersion of the thermoplastic nylon denture base in beetroot juice yields higher ΔE values than immersion in artificial saliva, a colorless solution. Both beetroot juice and artificial saliva caused color changes; however, these changes did not exceed the threshold for clinically perceptible color change (ΔE < 3.3), indicating that the discoloration was not visually obvious and remains clinically acceptable.